Robert Campbell (1808-1894) - Coates, Ken (ARCTIC, 1985)
. Campbell spent two unproductive years in the Dease Lake area, trying to break the Russian American Fur Company's hold on the interior fur trade. An agreement between the H.B.C. and R.A.F.C. in 1839 freed Campbell to turn his attentions northward. Thomas Simpson and Peter Warren Dease had, in 1837, crossed a major new river, which they named Colville, during their excursion along the arctic coast. Campbell, who had learned from the natives of the "Toutcho" or "Great Water" to the north, was directed to push to the north in search of the headwaters of this new river. He completed the exploration in two stages, reaching the Pelly River in 1840 and descending that stream to its junction with the Lewes (Yukon) River three years later. Governor Simpson ordered Campbell to establish a trading post at the promising "Forks," but poor trading and provisioning conditions at Frances Lake and Pelly Banks and Campbell's own hesitations stalled the expansion until 1848. These were hard times for Campbell and his men, as starvation threatened almost every year. Finally established at Fort Selkirk, he was directed to explore the remaining distance between that fort and Fort Yukon. His 1851 voyage proved that both posts were on the Yukon River and completed Campbell's contributions to the exploration of the North. . The strong opposition of the coastal Tlingit Indians to the H.B.C. presence culminated in an attack on Fort Selkirk in 1852 that left the post a charred ruin. . The governor would countenance no further expense on the unproductive field and sent Campbell on a long-overdue furlough to England. The trip provided him an opportunity to circulate news of his discoveries. In particular, he helped the Arrowsmiths, famous map makers, add the Pelly, Lewes, and Yukon rivers to the map of the far northwest. His accomplishments had been duly noted. . Still, his efforts helped bring the Hudson's Bay Company into the Yukon River valley and helped fill in one of the last remaining gaps on the map of North America. That alone was ...